A Novel Transformer Winding Fault Diagnosis Method Based on Damped Oscillation Wave. (August 2020) - Jin, Zhuorui; Sun, Jian; Yang, Qing; Su, Peiyu
Abstract: Winding status is an important part of transformer fault diagnosis. In this paper, the diagnosis test platform includes a reduced-scale transformer with the connection group model of Yn yn0, and its voltage ratio is 10 kV/0.4 kV. The voltage response of single-phase windings of three-winding transformers with varying degrees of short-circuit faults is measured under a damped oscillation wave with an amplitude of 4 kV and an equivalent frequency of 20 kHz. The transfer function of high-voltage phase and its corresponding low-voltage phase in the normal and fault condition is calculated. Three characteristic criterion of the transfer function are analysed in order to diagnose short-circuit faults in single-phase windings of three-winding transformers.